Research: Quality control in software documentation - Measurement of text comprehensibility - Lehner, Franz (Information & management, 1993)
The importance of software documentation and the effects of poor documentation in data processing are often underrated. Little research has been published that evaluates its quality. Software quality, on the other hand, is almost a buzzword. Discussions of software quality measurement often make reference to software documentation. However, the literature on the subject of software quality assurance has offered little adequate operationalization or usable instrument for quality measurement and quality control in software documentation. In the context of an explorative case study, a presentation is provided of existing comprehensibility measures for texts and an inventory of available tools, a summary of experience with comprehensiblity measures and tools published in the literature, the development of a tool for the computation of readability formulae, and the application of these measurement methods to software documentation.